Dual pathology in a patient with temporal lobe epilepsy associated with neocortical glial scar after brain abscess and end folium sclerosis/hippocampal sclerosis type 3. Issue 1 (22nd October 2020) - Miyata, Hajime; Sudo, Saeko; Kuwashige, Haruka; Miyao, Satoru; Nakamoto, Hidetoshi; Kubota, Yuichi; Yoshida, Yasuji
Abstract : End folium sclerosis or hippocampal sclerosis (HS) type 3 is often associated with another coexisting epileptogenic lesion (dual pathology); however, the pathogenesis of HS type 3 remains elusive. A 46‐year‐old man presented with medically intractable focal aware seizures and focal impaired awareness seizures (FIAS) with occasional focal to bilateral tonic–clonic seizures (FBTCS) two years after surgical treatment with extensive cranial reconstruction for a brain abscess in the right temporal lobe associated with intracranial extension of ipsilateral cholesteatoma. Head magnetic resonance imaging (MRI) at age 49 revealed atrophy of the right cerebral hemisphere including the hippocampus and amygdala. The patient's first epilepsy surgery was a lateral temporal lobectomy, in which the mesial temporal structures were preserved because no epileptiform discharge was detected on the intraoperative electrocorticogram. However, FIAS with FBTCS started 15 months after the operation. The second surgery, amygdalohippocampectomy, at age 52, resulted in the patient being seizure‐free again for one year before seizures of the right lateral temporal origin recurred. He underwent a third surgery, resection of the Heschl's and supramarginal gyri, at age 53, but he continued to have drug‐resistant epilepsy over two years after that. Histopathological examination revealed dual pathology consisting of glial scar in the lateral temporal lobe and ipsilateral HS type 3 with an unusually severe lesion in the subiculum. No significant inflammatory change was observed. The clinicopathological features in the present case indicate that HS developed secondarily in the context of neocortical epilepsy due to glial scar, suggesting a role of repetitive abnormal electrical input from neocortical epileptogenic lesions into the hippocampus finally via the perforant pathway in the pathogenesis of HS type 3. Severe hippocampal atrophy on preoperative MRI together with its silent electrocorticogram recording at initial epilepsy surgery may represent clinically pre‐epileptogenic HS in a seizure‐free "silent or latent period" before completion of hippocampal epileptogenesis to the extent that clinical epileptic seizures occur.